2011
DOI: 10.3109/14764172.2011.630082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incoherent LED radiation on third-degree burning wounds in rats

Abstract: The main physiological characteristics in a burn process are the increase of the capillary permeability and the occurrence of edema and exudation. Light-emitting diode (LED) has been proposed as treatment of burning. This study investigated the effects of LED on the repair process of rat skin submitted to a third-degree burning. The lesions were produced on the dorsal surface of male Wistar rats. Animals were divided into 4 groups (n = 6) as follows: L1 and L2 groups as LED-treated burned rats, and received LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
3
15
0
6
Order By: Relevance
“…Several studies have been reported that 630 nm and 640 nm LED irradia-tion with 4-24 J/cm 2 decreased wound surface area. 10,[15][16][17] Our results agree with the findings from several other studies that used 640 nm and 700 nm LED with 15-16 J/cm 2 to stimulate fibroblast proliferation and collagen production on excision wound in rats. 16,18,19 In the present study, epithelial gap of LED group showed signifi-…”
Section: Pcna Immunoreactive Fibroblastsupporting
confidence: 90%
“…Several studies have been reported that 630 nm and 640 nm LED irradia-tion with 4-24 J/cm 2 decreased wound surface area. 10,[15][16][17] Our results agree with the findings from several other studies that used 640 nm and 700 nm LED with 15-16 J/cm 2 to stimulate fibroblast proliferation and collagen production on excision wound in rats. 16,18,19 In the present study, epithelial gap of LED group showed signifi-…”
Section: Pcna Immunoreactive Fibroblastsupporting
confidence: 90%
“…Considering the data obtained at this experimental time for the LED group, this result is probably due to the action of phototherapy, making energy available to the cells that were damaged by the surgical process, thus accelerating the repair process during its secondary phase. 20,21,25,43,44 The most significant results were observed with the combination of LED and a semipermeable dressing (LED + D). It is noteworthy that the application of the dressing positively influenced the tissue repair process by accelerating it.…”
Section: Discussionmentioning
confidence: 75%
“…Breast milk is nutritionally ideal for the healthy development of a child and breastfeeding is ideal for orofacial growth and development. [ 8 , 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Phototherapy is the use of electromagnetic waves within the red and infrared spectra that are applied to biological tissues with the aid of low-level light devices, such as light amplification by stimulated emission of radiation (laser) and a light-emitting diode (LED). Studies have demonstrated the anti-inflammatory properties of phototherapy, with the enhancement of the wound repair process [ 11 13 ] and the control of pain. [ 14 , 15 ] As it does not cause discomfort, is relatively inexpensive, and may impede the discontinuation of breastfeeding, phototherapy could be a viable option for the treatment of nipple fissures.…”
Section: Introductionmentioning
confidence: 99%